Research Perspective: The Advantages of Using Plant-Derived Flavonoids as Natural Treatments in Aquaculture Compared to Not Using Them - Muh. Sulaiman Dadiono; Sri Andayani; Sutrisno Adi Prayitno; Aminin; Rima Oktavia Kusuma (Academic Letters, 2025)
Productivity in aquaculture activities is often reduced due to disease outbreaks caused by various pathogens, including bacteria, viruses, and parasites. As an alternative to chemical treatments, a natural, plant-based approach—particularly through the utilization of flavonoid compounds derived from medicinal herbs—is being developed as a safer and more sustainable solution. This paper presents the author’s perspective, based on previous research, on the advantages of using plant-derived flavonoids for the treatment of cultured fish and discusses the potential negative impacts that may arise if such compounds are not integrated into aquaculture systems.